Prospects for increasing commercial mushroom production in Malaysia: Challenges and opportunities - Rosmiza Mohd Zainol; Davies, WP; Rosniza Aznie CR; Jabil Mapjabil; Mazdi M (Mediterranean Center of Social and Educational Research, 2016)
One of the benefits of mushroom cultivation is their potential contribution to a more sustainable and environmentally-friendly way of farming. Mushroom cultivation using an agricultural waste as a growing medium, and the subsequent use of spent substrate has high value for horticultural activity; organic fertilizer; and potential utilise for animal feeding. The value of mushroom to diets, coupled with reported medicinal properties, can also provide valuable additional new small and mediumscale business options. This study attempts to evaluate the mushroom industry prospects in Malaysia. It also explores issues and challenges facing the mushroom industry in Malaysia by using a critical analysis and SWOT analysis. The main challenges include poor supply and the increasing price of raw material, for example sawdust; the poor quality of mushroom spawn, and the threat of diseases and pest attack. Several strategies are discussed to potentially improve the productivity of mushroom cultivation in Malaysia.